Perception of health status and quality of life of people living with HIV in Patan city, Gujarat, India: a cross sectional study - Dixit, Grishma T.; Thakor, Nilesh; Goswami, Mihir; Verma, P. B. (International Journal Of Community Medicine And Public Health, 2017)
Background: Human Immunodeficiency Virus is the biggest threat to the mankind today from their health perspective. To know the perception of health status and quality of life of people living with HIV/AIDS. Methods: This cross sectional study was undertaken during March 2015 to April 2016 at Patan city. After taking permission from NGO and Gujarat State AIDS Control Society (GSACS) total 100 purposively selected People living with HIV (PLHIV) attached to the NGO of Patan city were interviewed using predesigned semi-structured performa. Written informed consent was taken from all PLHIV. Ethical approval was obtained from institutional ethical committee for human research. Data safety and confidentiality was also given due consideration. Data were statistically analyzed using SPSS software (trial version). Results: Age of study population ranges from 18 to 68 years. Mean age of study population is 34.21 + 9.1 years. Maximum number of PLHIV, 51 % are in the age group of 31-40 years age group. Out of total, 76 have perception of being healthy .Out of total, 61 % PLHIV have faced stigma. Out of total,92% were enjoying life, 74% perceived good quality of life, 95% perceived safe in life, 96% perceived satisfaction with health services, 84% perceived satisfaction with their day to day work capability and only 8% perceived fear about their future life. Conclusions: Positive attitude towards life and health was observed in People Living with HIV.